Potential role of endoplasmic reticulum stress in doxorubicin-induced cardiotoxicity-an update - Sun, Mingli; Zhang, Xin; Tan, Boxuan; Zhang, Qingya; Zhao, Xiaopeng; Dong, Dan (Frontiers in Pharmacology, 2024)
As a chemotherapy agent, doxorubicin is used to combat cancer. However, cardiotoxicity has limited its use. The existing strategies fail to eliminate doxorubicin-induced cardiotoxicity, and an indepth exploration of its pathogenesis is in urgent need to address the issue. Endoplasmic reticulum stress (ERS) occurs when Endoplasmic Reticulum (ER) dysfunction results in the accumulation of unfolded or misfolded proteins. Adaptive ERS helps regulate protein synthesis to maintain cellular homeostasis, while prolonged ERS stimulation may induce cell apoptosis, leading to dysfunction and damage to tissue and organs. Numerous studies on doxorubicin-induced cardiotoxicity strongly link excessive activation of the ERS to mechanisms including oxidative stress, calcium imbalance, autophagy, ubiquitination, and apoptosis. The researchers also found several clinical drugs, chemical compounds, phytochemicals, and miRNAs inhibited doxorubicin-induced cardiotoxicity by targeting ERS. The present review aims to outline the interactions between ERS and other mechanisms in doxorubicin-induced cardiotoxicity and summarize ERS's role in this type of cardiotoxicity. Additionally, the review enumerates several clinical drugs, phytochemicals, chemical compounds, and miRNAs targeting ERS for considering therapeutic regimens that address doxorubicin-induced cardiotoxicity.